The effect of applied resources on competitive advantage in hotels: Mediation and moderation analysis - Cheraghalizadeh, Romina; Tumer, Mustafa (Elsevier, 2017)
Purpose: This study aims to consider the effects of organizational human and physical resources on customer relationship quality. It also investigates the effect of market and environmental dynamism as external factors in these associations. Furthermore, this study evaluates the mediation effect of customer relationship quality between applied resources and competitive advantage. Methodology: This research was implemented in North Cyprus. The number of hotel employees who participated was 297 with response rate of 85%. Convenience sampling method was considered for data collection of this study. Questionnaire was prepared in English and subjected to back-translation process afterwards. Nine employees were considered for the pilot study. Psychological separation and Harmans' single factor test were conducted as procedural and statistical potential remedies of common method bias. Exploratory factor analysis and Cronbach' alpha were applied to check existence of validity and reliability of questionnaire. Correlation and regression analysis were used to evaluate the relationship between variables and the method of Baron and Kenny (1986) was considered to evaluate mediation effects. Results: Findings indicated that managerial competence, employees' trait competitiveness and physical resources affect customer relationship quality positively. There is also a positive relationship between customer relationship quality and competitive advantage. Results showed that customer relationship quality fully mediates the relationship between managerial competence and competitive advantage; it also partially mediates the relationship between trait competitiveness and competitive advantage and also between physical resources and competitive advantage. Findings showed that environmental dynamism doesn't moderate the relationship between predictors and customer relationship quality, whereas market dynamism moderates the association between managerial competence and customer relationship quality as well as the relationship between trait competitiveness and customer relationship quality. However, market dynamism doesn't moderate the relationship between physical resources and customer relationship quality. The theoretical contribution: While several studies have focused the effect of various factors on customer behavior and organizational performance; there is still a paucity of empirical study to consider the effects of human and physical factors at the same time on organizational outcomes. This study evaluates this issue with a broader view and considers both internal and external factors to better understand which environment is more affective of organizational performance. Furthermore, North Cyprus is an island destination (Katircioglu et al., 2007) and they differ in notion of tourism image (Tasci et al., 2007). Therefore, there is still a need to study about success and failure factors in this kind of tourism destination. Practical implications: As the role of managers and employees are important in building a high quality relationship with customers, it is critical to hire competent managers and employees with a competitive spirit in the organization. To make new recruitments, motivation and personality of the applicants need to be considered. To enhance competition among employees, managers can apply different strategies such as setting an award and promotion system. Furthermore, for an organization to adapt to the market dynamism, managers have to understand the market and their competitors, make a plan, and hire qualified staff and so on. Participation in training courses is necessary to understand and learn more about employees, competitors and the market environment. (C) 2017 The Authors.
Keywords: Managerial competence; Trait competitiveness; Market dynamism; Environmental dynamism; Customer relationship quality; Competitive advantage